THE IMPACT OF SYRIAN IMMIGRATION SHOCK ON WAGES IN THE LEBANESE FASTFOOD LABOR MARKET - Baghdadi, Ibrahim; Banat, Rabih (European Scientific Journal, ESJ, 2014)
Fast-food is one of the largest industries in Lebanon. However, it offers the lowest wages. The factors that have the greatest influence on wage determination in the Lebanese fast-food labor market are, but not limited to, the seasonality aspect of the fast-food industry, the elasticity of demand for unskilled labor and the substantial labor supply shock from Syria. According to the economic theory, the marginal demand for unskilled labor, during the periods of high season, should shift the labor demand curve to the right and should, hence, increase wages. Unfortunately, this is not happening in Lebanon due to two main reasons: 1/the substitution effect due to minimum wage discrepancy; 2/ the surplus of unskilled workers (especially Syrians) who are not able to find jobs. In the presence of high own-wage elasticity that characterizes the demand for unskilled labor; wages were dropped and Lebanese workers have been easily substituted by Syrians. This paper studies the impact of a substantial immigration shock from Syria on the Lebanese fast-food labor market. Our study shows that despite the high demand for unskilled labor in periods of high season, wages reveal a marked decrease. As a conclusion, it is not evident that a boost in unskilledlabor demand will raise wages especially that the supply curve of unskilledlabor for fast-food business is more inelastic than the demand curve.